2010
DOI: 10.20969/vskm.2010.3(3).50-51
|View full text |Cite
|
Sign up to set email alerts
|

ExpEriEncE of combinEd (with roEntgEnothErapy) trEatmEnt of lymphorrhEa in thE groin aftEr artErial rEconstruction

Abstract: Реферат. Осложнением после реконструктивных операций на сосудах в области бедренного треугольника являет-ся лимфорея, что значительно удлиняет пребывание больного в стационаре. Рентгенотерапия с использованием малых доз облучения останавливает истечение лимфы из послеоперационных ран и способствует быстрому их заживлению. Ключевые слова: послеоперационная лимфорея, рентгенотерапия. ExpEriEncE of combinEd (with roEntgEnothErapy) trEatmEnt of lymphorrhEa in thE groin aftEr artErial rEconstruction I.I. Kamalov, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our data is consistent with what reported by Graz, Kazan and Zaporozhy. Low fraction doses of 0.3-0.5 Gy do not seem to be inferior to higher doses 10,12,14 . The "As low as reasonably achievable" (ALARA) fundamental principle of radioprotection is very well applicable to this clinical use of radiation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our data is consistent with what reported by Graz, Kazan and Zaporozhy. Low fraction doses of 0.3-0.5 Gy do not seem to be inferior to higher doses 10,12,14 . The "As low as reasonably achievable" (ALARA) fundamental principle of radioprotection is very well applicable to this clinical use of radiation.…”
Section: Discussionmentioning
confidence: 84%
“…Different doses of radiation have been proposed to treat lymphatic stulas 7,8,12,13 . In the largest study to date, Hautmann et al, reported the use of 3 x 3 Gy at the start of the treatment 7 with an increase to 3 additional fractions of 3 Gy for persistent stulas.…”
Section: Discussionmentioning
confidence: 99%
“…Different doses of radiation have been proposed to treat lymphatic fistulas [ 7 , 8 , 12 , 13 ]. In the largest study to date, Hautmann et al reported the use of 3 × 3 Gy at the start of the treatment [ 7 ] with an increase to 3 additional fractions of 3 Gy for persistent fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with what reported by Graz, Kazan and Zaporozhy. Low fraction doses of 0.3–0.5 Gy do not seem to be inferior to higher doses [ 10 , 12 , 14 ]. The “As low as reasonably achievable” (ALARA) fundamental principle of radioprotection is very well applicable to this clinical use of radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation